A perspective on the applications of functionalized nanogels: promises and challenges. (2nd January 2023) - Pinelli, Filippo; Saadati, Marjan; Zare, Ehsan Nazarzadeh; Makvandi, Pooyan; Masi, Maurizio; Sacchetti, Alessandro; Rossi, Filippo
ABSTRACT: In the last two decades nanogels have emerged as very promising and versatile biomaterials suitable for a wide range of applications. Their features such as large surface area, ability to hold molecules, flexibility in size and water-based formulations have ensured them great recognition as drug delivery systems with various in vivo applications which have confirmed their potential. On the other handnanogels have been investigated in recent years for applications in various fields other than biomedicine. Clear examples of this are represented by the possibility of employing nanogels as sensing materials, as catalysts or as adsorbents for environmental applications. In view of this variety of possible applications, in this work we extend our knowledge on the topic of their possible uses described in literature, taking stock of the state of the art for all possible nanogel employment and their synthesis methods.